The Impact of Trust on Entrepreneurship in Poland - Marta Młokosiewicz; Sandra Misiak-Kwit (Journal of Entrepreneurship, Management and Innovation)

(untitled)
In the global rankings of generalized trust, Poland occupies a lowly positon. Only 1/3 of Poles have a strong trust in strangers and roughly the same number believe that trust in business generally pays of. At the same tme, only half of them believe that a market economy based on private enterprise is the best economic system for the country. According to the literature review a major factor in the development of entrepreneurship is trust in other economic actors. The aim of the artcle is to present the relaton between trust and entrepreneurial actvites in Poland. In this paper the hypothesis was adopted that the level of trust in the public sphere, especially in business relatons in Poland, had an impact on the intensity of entrepreneurial actvites. The analysed period comprises the years from 2002 to 2016. The artcle presents changes in the potental for social trust, including trust in business. Indicators of confdence include the percentage of people that have trust in diferent actors in Poland. A further part of the paper is devoted to the phenomenon of entrepreneurship in Poland. Among the indicators of entrepreneurship are the number of newly registered and deregistered enttes, and enttes that are new or deregistered from the REGON register per 10 thousand of populaton. Moreover, the innovaton actvity of enterprises in Poland has been described. At the end, relatons between trust and entrepreneurial actvites in Poland were examined. The data was analysed statstcally with Pearson’s correlaton coefcients. The analysis of confdence and entrepreneurship is based mainly on the data published by the Polish Central Statstcal Ofce and Public Opinion Research Centre.